2011
DOI: 10.1159/000327936
|View full text |Cite
|
Sign up to set email alerts
|

Necrobiosis Lipoidica: Early Diagnosis and Treatment with Tacrolimus

Abstract: We present a case of necrobiosis lipoidica (NL) with atypical early lesions and good response to topical tacrolimus. NL is a disease with clinical features that are seldom misinterpreted. Often histology just confirms the clinician’s diagnosis. Only in rare cases, the clinical presentation and the involved body sites may be misleading. A 67-year-old diabetic woman was admitted to our department with a well-defined, persistent plaque on her left arm and on her right shin. Histologic examination of both lesions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…Recent reports have also described the therapeutic effect of neutralization of proinfiammatory cytokines (e.g. TNF-a) on NL (1, 3). In this report, we describe a case of pigmented NL presenting atypical clinical features, accompanied by IDDM.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Recent reports have also described the therapeutic effect of neutralization of proinfiammatory cytokines (e.g. TNF-a) on NL (1, 3). In this report, we describe a case of pigmented NL presenting atypical clinical features, accompanied by IDDM.…”
Section: Discussionmentioning
confidence: 69%
“…Insulin-dependent type 1 diabetes mellitus (IDDM) is a chronic autoimmune disease caused by the selective destruction of pancreatic insulin-producing B cells (3). Autoimmunity comrnonly occurs when central or peripheral tolerance barriers are broken down, allowing the activation of self-reactive T cells (4).…”
mentioning
confidence: 99%
“…Some authors have reported a beneficial effect from smoking cessation and blood glucose control. Other therapeutic options are antiplatelet agents, cyclosporine, thalidomide, clofazimine, anti-TNF agents, fumaric acid esters, PUVA, photodynamic therapy, hydroxychloroquine, and tacrolimus 7 - 13 …”
Section: Discussionmentioning
confidence: 99%
“…Microangiopathy, immune complex vasculitis with involvement of T cells, release of proinflammatory cytokines, and abnormal collagen production have all been implicated [11]. Several different therapies have been reported with limited success in the literature, including topical and systemic corticosteroids, nicotinamide, pentoxifylline, tretinoin, anti-TNF- α , mycophenolate mofetil, thalidomide, cyclosporine, tacrolimus, dipyridamole-aspirin, antimalarials, and PUVA [1214]. …”
Section: Discussionmentioning
confidence: 99%